Australian Emergency Department health professionals' reasons to invite or not invite Family Witnessed Resuscitation: A qualitative perspective - Chapman, Rose; Bushby, A.; Watkins, R.; Combs, S. (2014)
Background: Debate continues regarding the effectiveness of Family Witnessed Resuscitation and little is known about the reasons why staff invite family presence. Aim: Explore why health professionals invite or not invite Family Witnessed Resuscitation. Design: Descriptive qualitative study. Method: Three open-ended questions enabled 114 clinicians to describe why they would or would not invite family presence. Data were analysed using qualitative data analysis. Results: Four themes representing factors that influenced staff decision to invite or not invite Family Witnessed Resuscitation were identified: motivating factors, personal choice, staff judgment, and organisational factors. Motivating factors described reasons to invite family presence, and staff and organisational factors were reasons to not invite family presence. Conclusion: Family presence can be beneficial for staff and family and is likely to be motivated by family-specific factors where this choice is appropriate for all stakeholders. Participants described factors that can impact on the appropriateness of inviting family presence and these need to be considered before an invitation is extended. Relevance to practice: To support all parties throughout the process it is imperative that a skilled support person be available to the family and that written policies and guidelines be available for staff.